2005
DOI: 10.1093/gerona/60.6.777
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Maximal Isometric and Isokinetic Resistance Training on Strength and Functional Mobility in Older Adults

Abstract: It was clear that all three resistance training programs (isometric, concentric, and eccentric) in older adults were effective in increasing strength, concentric work, and concentric power over the 12-week training period. Furthermore, 12 weeks of resistance training resulted in improved stair ascent and descent performance.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

8
65
3
15

Year Published

2007
2007
2019
2019

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 93 publications
(91 citation statements)
references
References 21 publications
8
65
3
15
Order By: Relevance
“…Among those with poor total isokinetic work levels, isokinetic resistance exercise may provide a safe (27) and controlled modality to improve isokinetic work, strength, and function. Indeed, previous trials of resistance exercise training among older adults across a range of physical performance have demonstrated that lower extremity resistance training increases total muscle work translating into improvements in stair descent and balance (28,29). Additionally measurement of total isokinetic work may safely assess effectiveness of rehabilitative interventions or efficacy of drug therapies targeting improvements in muscle-specific performance and endurance.…”
Section: Discussionmentioning
confidence: 99%
“…Among those with poor total isokinetic work levels, isokinetic resistance exercise may provide a safe (27) and controlled modality to improve isokinetic work, strength, and function. Indeed, previous trials of resistance exercise training among older adults across a range of physical performance have demonstrated that lower extremity resistance training increases total muscle work translating into improvements in stair descent and balance (28,29). Additionally measurement of total isokinetic work may safely assess effectiveness of rehabilitative interventions or efficacy of drug therapies targeting improvements in muscle-specific performance and endurance.…”
Section: Discussionmentioning
confidence: 99%
“…Fortunately, resistance training has been shown to offset many age-related declines in functional performance. [3][4][5] As sarcopenia contributes to decreased muscle function, exercise programs that can minimize or combat the loss of muscle mass, strength, and power can have significant implications on how older adults function. 6 Recently, whole-body vibration (WBV) has emerged as an alternative strength training intervention, with gains reported to be comparable to resistance training in young adults who were healthy.…”
mentioning
confidence: 99%
“…Nous avons montré que les hommes et les femme âgés pourraient bénéficier également d'un entraînement contre résistance isométrique, concentrique ou excentrique (Symons et al 2005). Les exercices excentriques soulèvent une préoccupation, soit qu'ils risquent davantage de causer peut-être des lésions aux muscles, aux tendons et aux articulations.…”
Section: Résumé Des Aspects Neuromusculaires Et De L'entraînement Conunclassified